An empirical analysis of quantitative investment strategies based on governance factors - Tornieporth, Felix (2021)
This work project examines and quantifies the financial impact of corporate governance on the performance of portfolios in European capital markets. Corporate governance refers to a set of rules, practices and procedures by which a company is managed and controlled. In this paper, four different scores, Corporate Governance as an overall score and three sub-themes: Management, Shareholders and CSR Strategy, are used as investment factors. Various portfolios are constructed and evaluated based on these factors. The hypothesis that higher scores in corporate governance lead to higher risk-adjusted returns cannot be proven, neither for the governance pillar nor its three sub-themes.